2018
DOI: 10.13057/biodiv/d190546
|View full text |Cite
|
Sign up to set email alerts
|

Leunca (Solanum americanum Mill.): The uses as vegetable in two villages in Upper Citarum Area, Bandung, West Java, Indonesia

Abstract: Abstract. Prihatini J, Iskandar J, Partasasmita R, Nurjaman D. 2018. The impacts of traditional homegarden conversion into the commercial one: A case study in Sukapura Village of the Upstream Citarum Watershed, West Java, Indonesia. Biodiversitas 19: 1926-1940. In the past, rural homegardens in West Java were planted with various annual and perennial crops. As a result, the vegetation structure of traditional homegardens in rural areas of West Java, Indonesia was very complex, similar to that of forest vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In a study of homegardens in Vietnam (Timsuksai et al 2015) ornamental plants ranked second, while in homegardens of Karwar, Karnataka, India, ornamental plants ranked first, indicating that the economic level of the community was relatively good (Bhat et al 2014). In West Java, the transition of traditional homegardens into the modern ones was characterized by the increase in proportion of ornamental species (Iskandar et al 2018;Prihatini et al 2018). Although the number of useful species varied greatly among the traditional gardens, in general, the diversity of useful plant species in traditional gardens is much higher that of modern plantations.…”
Section: The Diversity Of Useful Plant Species and Types Of Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of homegardens in Vietnam (Timsuksai et al 2015) ornamental plants ranked second, while in homegardens of Karwar, Karnataka, India, ornamental plants ranked first, indicating that the economic level of the community was relatively good (Bhat et al 2014). In West Java, the transition of traditional homegardens into the modern ones was characterized by the increase in proportion of ornamental species (Iskandar et al 2018;Prihatini et al 2018). Although the number of useful species varied greatly among the traditional gardens, in general, the diversity of useful plant species in traditional gardens is much higher that of modern plantations.…”
Section: The Diversity Of Useful Plant Species and Types Of Usesmentioning
confidence: 99%
“…However, many traditional gardens have been converted into commercial ones due to the penetration of market economy which causes drastic changes in their species composition. In Sukapura Village of West Java, Prihatini et al (2018) found that traditional gardens were composed of 161 species of plants, while the commercial gardens had only 61 species, dominated by commercial vegetable crops. Although the commercial gardens yield high economic revenue, they lose some of their ecological functions.…”
Section: The Diversity Of Useful Plant Species and Types Of Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakarangan itself is usually used by the community as a place to grow vegetables such as cengek (Capsicum frutescens L) or herbs. The plots of land in Cintaratu Village generally tend to have lower diversity of plant species than the home-gardens in semi-urban areas such as in Sukapura village, Bandung, which have many species of vegetable crops, including corn (Zea mays L), cassava (Manihot esculenta Crantz), banana (Musa x paradisiaca L), tomato (Solanum lycopersicum L), ginger (Zingiber officinale Roscoe), sand ginger / Kaempferia galanga L), tumeric / koneng (Curcuma domestica Valeton), sweet potato / hui boled (Ipomoea batatas L), peanut (Arachis hypogaea L), and lemongrass (Cymbopogon citratus (DC) Stapf) (Prihatini et al 2018).…”
Section: Changes Of the Landscapes In The 2000s-2019mentioning
confidence: 99%
“…(Iskandar 2017;. Generally, food choice in the community is not simply an individual behavior but a practice influenced by social and environmental conditions, and these environments vary greatly, contributing to growing natural health inequalities (Engler-Stringer et al 2014;Pieroni et al 2016;Mulyanto et al 2018).…”
Section: Introductionmentioning
confidence: 99%